Impaired exercise capacity after lung transplantation is related to delayed recovery of muscle strength. (2nd July 2013) - Walsh, James R.; Chambers, Daniel C.; Davis, Rebecca J.; Morris, Norman R.; Seale, Helen E.; Yerkovich, Stephanie T.; Hopkins, Peter M.A.
Abstract Lung transplant recipients report reduced exercise capacity despite satisfactory graft function. We analysed changes in lung function, six‐min walk distance (6MWD), and quadriceps strength in the first 26‐wk post‐transplant and examined what factors predict 6MWD recovery. All lung transplant recipients at a single institution between June 2007 and January 2011 were considered for inclusion. Lung function, 6MWD, and quadriceps strength corrected for body weight (QS%) were recorded pre‐ and two‐, six‐, 13‐, and 26‐wk post‐transplant. Fifty recipients, of mean (±SD) age 42 (±13) yr, were studied. Mean FEV1% and 6MWD improved from 26.4% to 88.9% and from 397 to 549 m at 26 wk, respectively (both p < 0.001). QS% declined in the first two wk but had improved to above pre‐transplant levels by 26 wk (p = 0.027). On multivariate analysis (n = 35), lower pre‐transplant exercise capacity and greater recovery in muscle strength explained most of the improvement in exercise capacity. Delayed recovery of exercise capacity after lung transplantation is unrelated to delay in improvement in graft function, but occurs secondary to the slow recovery of muscle strength. Our findings show that additional controlled trials are needed to better understand the influence of exercise rehabilitation on improvement in exercise capacity post‐transplantation.